REFORMULASI PEMIKIRAN ASWAJA: UPAYA MEMPERKECIL SIKAP IDIOLOGI KEAGAMAAN MUSLIM NAHDHIYIN - Syahrul Khoiron; Reza Ahmad Zahid; Ahmad Ali Riyadi (PT. Saha Kreasi Indonesia, 2025)
Ahlussunnah wal Jamaah (Aswaja) is a classical religious concept that has deeply rooted itself in the life of the Nahdliyin Muslim community. Initially, Aswaja was regarded as an exclusive doctrine belonging solely to the Nahdliyin group; however, over time, awareness has grown that Aswaja is also recognized and practiced by various other Islamic groups with diverse interpretations and approaches. This diversity of interpretation has led to differences in theological, political, and practical aspects of religious life, which at times have caused fragmentation among Muslims themselves. Historically, Aswaja emerged as a response to the dynamic development of Islamic thought and evolved through the contributions of figures such as al-Ash’ari, al-Maturidi, al-Ghazali, and al-Junaid. These scholars laid the foundation for a moderate, inclusive, and accommodative religious worldview. Nevertheless, in practice, some Nahdliyin Muslims still tend to understand Aswaja normatively and dogmatically, without engaging in a progressive intellectual dialectic. As a result, the scholarly tradition within the Nahdliyin community tends to stagnate and become trapped in sectarian fanaticism. To revive a dynamic intellectual spirit, it is necessary to reconstruct the understanding of Aswaja from a normatively moderate model toward a progressively moderate one. This transformation can be achieved by opening space for critical reflection, innovation, and the development of knowledge relevant to contemporary challenges. Ontological, epistemological, and axiological studies of Nahdliyin’s intellectual tradition are therefore essential in rebuilding an adaptive, critical, and human-oriented scientific awareness that contributes to the broader welfare of the Muslim community.